The Influence of Boy-Boyan Games on the Social-Emotional Abilities of Children Aged 5-6 Years at TK Siaga Muda, Percut Sei Tuan District - Nadhila, Anggun Aulia; Kamtini (International Journal of Applied and Advanced Multidisciplinary Research, 2023)
This study aims to find out the influence of boy-boyan games on the social-emotional abilities of children aged 5-6 years in TK Siaga Muda. This research was conducted at TK Siaga Muda, with a population of 20 children which made a sample of 10 children. In this study, the method used is the One Group Pre-Test Post-Test research method. Based on the results of Wilcoxon calculations, the number of steps marked positive = 45, and the number of steps marked negative = -10. So, Jcount = ie the number of smaller levels. If Jcount is compared with Jtable N 10 with α 0.05 then Jtable = 8. From the results of the above analysis, it can be said that Jcount > Jtable where >, thus the hypothesis is accepted. It means "There is a significant effect of Boy-boyan Games on the Social Emotional Ability of Children Aged 5-6 Years in TK Siaga Muda ".